Malaysian good agricultural practices (mygap): inflential factors for adoption by farmers in Negeri Sembilan, Malaysia - Abd Rahman, Muhamad Aiman; Ismail, Nur Amalina; Bakar, Muhammad Aliuddin; Syahlan, Syarizan; Zulkifli, Farahida (GADING Journal for the Social Sciences, 2024)
MyGAP, a certification programme for agriculture, aquaculture, and livestock, emphasises environmental, economic, and social aspects to ensure product safety and quality. This research focuses on understanding farmers' intentions and motivation levels regarding adopting MyGAP in Negeri Sembilan. Data from 367 farmers was gathered using a survey method through online and face-to-face interviews. The farmers were selected using simple random sampling from the population. The research employed various analytical methods: descriptive, Pearson correlation, and multiple regression. The findings reveal a significant and positive correlation (p < 0.001) between each variable and the adoption of MyGAP. Notably, perceived behavioural control (β = 0.380) emerged as the primary factor influencing MyGAP adoption. Implementing MyGAP is anticipated to enhance farm production, income, and marketability in the long term. It represents a move towards increasing the resilience of agricultural systems through sustainable practices, marking a significant stride in the sector's development.